Fault-Tolerant Adaptive Routing Algorithm for 2D Torus Network - Miura, Yasuyuki; Nakao, Tsukasa-Pierre; Fukase, Naohisa (Discoveries in Agriculture and Food Sciences, 2019)
A 2D torus network is one of the most popular networks for parallel processing. We have researched the North-South First (NSF) routing which is applicable to a 2D torus and combines the north-first (NF) and south-first (SF) methods.  We focused on the proposal of a routing algorithm aimed at avoiding congestion of the crowded network. It was superior in congestion tolerance but not in fault tolerance. We have therefore been researching algorithms considering fault tolerance of the NSF method. In this paper we propose an NSF-FT method which is a new routing algorithm with improved fault tolerance. We evaluated the congestion resistance and fault tolerance of the proposed method by dynamic communication performance evaluation by simulation. The software simulation showed that the proposed algorithm has higher performance.